2020
DOI: 10.1103/physrevb.102.064425
|View full text |Cite
|
Sign up to set email alerts
|

Determination of spin Hall angle, spin mixing conductance, and spin diffusion length in CoFeB/Ir for spin-orbitronic devices

Abstract: Iridium is a very promising material for spintronic applications due to its interesting magnetic properties such as large RKKY exchange coupling as well as its large spin-orbit coupling value. Ir is for instance used as a spacer layer for perpendicular synthetic antiferromagnetic or ferrimagnet systems. However, only a few studies of the spintronic parameters of this material have been reported. In this paper, we present inverse spin Hall effect -spin pumping ferromagnetic resonance measurements on CoFeB/Ir ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 54 publications
3
21
1
Order By: Relevance
“…, the effective spin Hall angles of Pt/SmCo 5 /Ta, Pt/SmCo 5 /W and Pt/SmCo 5 /Ir can be obtained as 0.68, 0.53, and 0.29, respectively. These values are in agreement with the sum of the reported spin Hall angles of Pt (+0.02-0.15), [46,28] Ta (−0.15 to −0.25), [47,48] W (−0.18 to −0.36), [45,49] and Ir (0.01-0.02) [50,51] films, and are similar with the results from the Pt/ Co/Ta [44] and W/CoTb/Pt [45] trilayers.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…, the effective spin Hall angles of Pt/SmCo 5 /Ta, Pt/SmCo 5 /W and Pt/SmCo 5 /Ir can be obtained as 0.68, 0.53, and 0.29, respectively. These values are in agreement with the sum of the reported spin Hall angles of Pt (+0.02-0.15), [46,28] Ta (−0.15 to −0.25), [47,48] W (−0.18 to −0.36), [45,49] and Ir (0.01-0.02) [50,51] films, and are similar with the results from the Pt/ Co/Ta [44] and W/CoTb/Pt [45] trilayers.…”
Section: Resultssupporting
confidence: 91%
“…and Ir (0.01~0.02) [50,51] films, and are similar with the results from the Pt/Co/Ta [44] and W/CoTb/Pt [45] trilayers.…”
Section: Resultssupporting
confidence: 86%
“…Recently Fache et al., reported spin pumping in CoFeB/Ir bilayers. [ 29 ] However, in our case we could not observe any ISHE voltage in CoFeB/Ir system. This might be due to the interface in the samples and/or the low power used in our set‐up.…”
Section: Resultscontrasting
confidence: 69%
“…Our ST‐FMR results in the Pt/CoGd/X series are consistent with the reported SHA values of W, Ta, and Ir in the literature. [ 25 , 26 , 27 , 43 ] Indeed, it was demonstrated that W and Ta have a much larger SHA than Pt and of opposite sign. [ 25 , 26 , 27 ] Due to the chirality of the spin‐orbit interactions at the top and bottom interface in Pt/CoGd/(W or Ta), spin currents from the two adjacent layers add up leading to a maximized SOT efficiency.…”
Section: Resultsmentioning
confidence: 99%